2022
DOI: 10.51791/njap.v48i6.3278
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of dynamics and prevalence of microbial flora of soaked dry meats (Kundi and Ponmo) in Nigeria

Abstract: The manner in which dry meat is prepared in under developed countries is highly unhygienic. Preserved meats (kundi and ponmo) were obtained from three food markets in Ibadan and were properly labelled. Samples cut into 50 grams were taken to the laboratory and soaked for 0, 6, 12, 18 and 24 hours. Water used for soaking and homogenised meat samples were cultured for Salmonella, Campylobbacter, E. coli, total bacterial count (TBC), total coliform count (TCC). Data were subjected to analysis of variance (ANOVA).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 1 publication
(1 reference statement)
3
3
0
Order By: Relevance
“…The microbial count in this current work was high for all the samples (range between 1.1 x 10 6 in wet white ponmo (WWP) to 1.4 x 10 7 in both brown ponmo water (BPW) and wet brown ponmo (WBP), this result is consistent with [ [ 4 , 6 , 24 ]] who all reported a similar high microbial load as well. The least microbial load obtained in the WWP may be because it is still relatively fresh from the slaughterhouse and has not been exposed to other environmental factors and handling that could have contributed to an increase in the bacterial load.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…The microbial count in this current work was high for all the samples (range between 1.1 x 10 6 in wet white ponmo (WWP) to 1.4 x 10 7 in both brown ponmo water (BPW) and wet brown ponmo (WBP), this result is consistent with [ [ 4 , 6 , 24 ]] who all reported a similar high microbial load as well. The least microbial load obtained in the WWP may be because it is still relatively fresh from the slaughterhouse and has not been exposed to other environmental factors and handling that could have contributed to an increase in the bacterial load.…”
Section: Discussionsupporting
confidence: 90%
“…The least microbial load obtained in the WWP may be because it is still relatively fresh from the slaughterhouse and has not been exposed to other environmental factors and handling that could have contributed to an increase in the bacterial load. The highest microbial count obtained from BPW and WBP is corroborated with the report of [ 6 ] who reported a Total Bacterial Count of 4.1 x 10 5 cfu/g of meat product tissue soaked in water. He also analyzed the effect of the duration of soaking of kundi on microbial load in water and found that the microbial load increased with an increase in the soaking time or duration [ 6 ].…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations